Piezoelectric membrane for separation process - Peh, Min Xian (Nanyang Technological University, 2022)
This report compares the fouling control performance of electrically poled piezoelectric PVDF membranes with PVDF membranes subject to air bubbling, using a feed of diluted wastewater. Overall, the piezoelectric membrane demonstrated improved fouling control when compared to air bubbling in terms of lengthening the time required for the onset of fouling, a better quality of permeate as well as reducing foulant accumulation on the membrane surface, at a lower specific energy consumption.